Use of alpha-chloralose to remove waterfowl from nuisance and damage situations - Woronecki, Paul P.; Dolbeer, Richard A.; Seamans, Thomas W. (eScholarship, University of California, 1990)
From 1988 through early 1990 alpha-chloralose (A-C) was successfully used in the United States to immobilize and remove 70 Canada Geese (Branta canadensis), 315 mallard, domestic and hybrid ducks (Anas platyrhynchos), and 348 coots (Fulica americana) from 17 commercial and residential sites including golf courses, pools, and ponds. Field trials and baiting techniques with bread and corn are described. The optimum dose of A-C for geese, ducks, and coots, using orally administered bread and corn baits, was about 20-30 mg/kg. We are currently pursuing registration of A-C as a bird control chemical with the U.S. Food and Drug Administration.